Report by Dawson on his work in Newcastle to publish the British Worker, 27 May 1926 (page 4)
1926-05-27 "Report by Dawson on his work in Newcastle to publish the British Worker, 27 May 1926 (page 4)" [g0736004.jpg], 27 May 1926, Dawson